Practical stability performance of polyvinylether(PVE)with HFC refrigerarits - 富永正一; 高木实 (Zhileng xuebao)
Deterioration degree of PVE Lubricants was investigared by analyzing used oils after various compressor and system tests with HFC refrigerants. As a result,deterioration of PVE itself was not observed and long term reliability was confirmed. Furthermore,autoclave tests with water and air were performed to determine the reliability limit of PVE in comparison with mineral oil and polyolester. Through these studies, it was conrirmed that PVE with HFC refrigerant has enough tolerance to air or watre contamination to secure long term reliability.